Crop nutrient management using Nutrient Expert improves yield, increases farmers’ income and reduces greenhouse gas emissions - Sapkota, Tek Bahadur; Jat, Mangi Lal; Rana, Dharamvir Singh; Khatri-Chhetri, Arun; Jat, Hanuman Sahay; Bijarniya, Deepak; Sutaliya, Jhabar M; Kumar, Manish; Singh, Love Kumar; Jat, Raj K.; Kalvaniya, Kailash C.; Prasad, Gokul; et al. (Springer, 2021)
Reduction of excess nutrient application and balanced fertilizer use are the key mitigation options in agriculture. We evaluated Nutrient Expert (NE) tool-based site-specific nutrient management (SSNM) in rice and wheat crops by establishing 1594 side-by-side comparison trials with farmers’ fertilization practices (FFP) across the Indo-Gangetic Plains (IGP) of India. We found that NE-based fertilizer management can lower global warming potential (GWP) by about 2.5% in rice, and between 12 and 20% in wheat over FFP. More than 80% of the participating farmers increased their crop yield and farm income by applying the NE-based fertilizer recommendation. We also observed that increased crop yield and reduced fertilizer consumption and associated greenhouse gas (GHG) emissions by using NE was significantly influenced by the crop type, agro-ecology, soil properties and farmers’ current level of fertilization. Adoption of NE-based fertilizer recommendation practice in all rice and wheat acreage in India would translate into 13.92 million tonnes (Mt) more rice and wheat production with 1.44 Mt less N fertilizer use, and a reduction in GHG of 5.34 Mt CO2e per year over farmers’ current practice. Our study establishes the utility of NE to help implement SSNM in smallholder production systems for increasing crop yields and farmers’ income while reducing GHG emissions.